Measuring the microbial load of airborne microbes in some Jizan region hospitals - Alharbi, Mohammed Ghallab; Balkhyor, Mansour Ahmed; Madkoor, Mohammed Hussain (Journal of medical and pharmaceutical sciences, 2020)
This research aims to reveal the current situation in the field of occupational exposure to microbes By measuring the microbial load of airborne microbes In some Jizan region hospitals, the hospitals in which the study was conducted are: King Fahd Central Hospital, Prince Muhammad bin Nasser Hospital, Damad General Hospital, Sabya General Hospital and Al- Umais Hospital (private). The maximum bacterial load was 1900cfu/m3, emergency room in King Fahd Central Hospital, and the minimum bacterial load was 60cfu/m3 in lab department in Alemies hospital. The maximum fungal load value was 90cfu/m3 in emergency room, Prince Mohammed Hospital, and the minimum fungal load was 7cfu/m3 in lab department inside Damad General Hospital. Correlation coefficient between bacteria and fungi in King Fahd Hospital, Prince Muhammad, Al- Umais, Damad and Saba. There is a very strong direct correlation with statistical significance (0,04) between bacteria in King Fahd Hospital and fungi in Prince Muhammad Hospital. The correlation coefficient was equal to (0.998), there is a direct correlation Very strong and statistically significant (0,02) between bacteria in King Fahd Hospital and bacteria in Saba Hospital, and the correlation coefficient was equal to (0.999),and there is also a complete statistically significant correlation (0,02) between fungi in Prince Muhammad Hospital and bacteria in Saba Hospital, and the correlation coefficient was equal to (1),